1965
DOI: 10.2466/pms.1965.20.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Deprivation Tolerance and Adequacy of Defenses

Abstract: The Rorschach test was administered to 14 Ss who had endured a week of perceptual deprivation and to 7 Ss who had terminated isolation prematurely. An Index of Control, equivalent to the proportion of Defense Demand to Effectiveness of Defense, was derived for each S. Groups with High- and Mid-control Indices tended to be composed of successful Ss whereas the group with a Low-control Index tended to be composed of unsuccessful isolation Ss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1965
1965
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…If so, then the ability to integrate primary process material is related to the ability to cope with feelings of internal distress. This speculation is consistent with a number of studies in the adult area, which have shown that the degree of primary process integration is significantly positively related to tolerance for psychological stress and the willingness to endure it (Goldberger, 1961;Heath, 1965;Lipman, 1979;Wright & Abbey, 1965;Wright & Zubeck, 1969).…”
Section: Discussionsupporting
confidence: 74%
“…If so, then the ability to integrate primary process material is related to the ability to cope with feelings of internal distress. This speculation is consistent with a number of studies in the adult area, which have shown that the degree of primary process integration is significantly positively related to tolerance for psychological stress and the willingness to endure it (Goldberger, 1961;Heath, 1965;Lipman, 1979;Wright & Abbey, 1965;Wright & Zubeck, 1969).…”
Section: Discussionsupporting
confidence: 74%
“…The perceptual deprivation situation has been conceptualized as an "unstructured behavioral projective test" (Freedman & Greenblatt, 1959). In view of this, it has been suggested (Wright & Abbey, 1965) that the Borschach test may be a better measure of perceptual deprivation tolerance than a variety of paper and pencil tests of personality since it elicits a sample of how the individual typically structures ambiguous situations according to his needs. The purpose of Experiment II was to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…One measure that did not hold up was the Rorschach measure of adaptive regression, which had worked well in the original sample but trended in the opposite direction with the actors. It did, however, prove a sturdy predictor in several studies of sensory deprivation conducted outside our own laboratory (Wright & Abbey, 1965;Wright & Zubek, 1969;Zubek, 1969).…”
Section: Perceptual Isolation (Sensory Deprivation)mentioning
confidence: 88%